Impaired functionality of antigen presenting cells in HIV- exposed uninfected infants in the first six months of life - Jalbert, Emilie; Ghosh, Tusharkanti; Smith, Christiana; Amaral, Fabiana R.; Mussi-Pinhata, Marisa M.; Weinberg, Adriana (Frontiers in Immunology, 2022)
HIV-exposed uninfected infants (HEU) have increased morbidity and mortality due to infections in the first 6 months of life that tapers down to 2 years of life. The underlying immunologic defects remain undefined. We investigated antigen-presenting cells (APC) by comparing the phenotype of unstimulated APC, responses to toll-like receptor (TLR) stimulation, and ability to activate natural killer (NK) cells in 24 HEU and 64 HIV-unexposed infants (HUU) at 1-2 days of life (birth) and 28 HEU and 45 HUU at 6 months of life. At birth, unstimulated APC showed higher levels of activation and cytokine production in HEU than HUU and stimulation with TLR agonists revealed lower expression of inflammatory cytokines and activation markers, but similar expression of IL10 regulatory cytokine, in APC from HEU compared to HUU. Differences were still present at 6 months of life. From birth to 6 months, APC underwent extensive phenotypic and functional changes in HUU and minimal changes in HEU. TLR stimulation also generated lower NK cell expression of CD69 and/or IFNγ in HEU compared with HUU at birth and 6 months. In vitro experiments showed that NK IFNγ expression depended on APC cytokine secretion in response to TLR stimulation. Ex vivo IL10 supplementation decreased APC-mediated NK cell activation measured by IFNγ expression. We conclude that APC maturation was stunted or delayed in the first 6 months of life in HEU compared with HUU. Deficient inflammatory APC responses and/or the imbalance between inflammatory and regulatory responses in HEU may play an important role in their increased susceptibility to severe infections.